Un intento de hacer ciencia para enseñar ciencias - Comín del Río, P. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
A methodological didactic experience is presented on the unit «the soil as nexus between Geology and Biology» as an example of learning through discovering.